Celí: o design lúdico ajudando a lidar com a doença celíaca - Arioli, Janaíne (My University, 2021)
This project consists of presenting a solution for tutors and children to obtain information about celiac disease. In the first part, there is extensive research on important issues that collaborated in the development of the solution portrayed, involving relevant data on celiac disease, children's eating behavior, the use of playfulness in learning, and multisensory design. Interviewing the target audience and professionals relevant to the theme were essential in acquiring fundamental information for the project and, along with co-creation, directing this project towards the elaboration of a final product that would meet the proposed needs. The result achieved was a project that unites visual identity, product, and service. [resumo fornecido pelo autor]
Este projeto consiste em apresentar uma solução acerca da obtenção de informações sobre a doença celíaca por tutores e crianças. Na primeira parte, há uma extensa pesquisa sobre assuntos importantes que colaboraram no desenvolvimento da solução retratada, envolvendo dados relevantes sobre a doença celíaca, comportamento alimentar infantil, a utilização do lúdico na aprendizagem e o design multissensorial. Entrevistas com o público-alvo e profissionais relevantes ao tema foram essenciais na aquisição de informações fundamentais ao projeto e, junto à cocriação, direcionar este projeto para a elaboração de um produto final que atendesse às necessidades propostas. O resultado alcançado foi um projeto que une identidade visual, produto e serviço. [resumo fornecido pelo autor]
Keywords: Design; Doença celíaca; Doença celíaca em crianças; Educação; Crianças